Media consumption among young adults: a look at labels and norms in everyday life - Latiffah Pawanteh,; Samsudin A. Rahim,; Fauziah Ahmad, (Universiti Kebangsaan Malaysian, 2009)
Globalisation has been criticised for challenging national sovereignty and cultural identities. Although its cultural homogenising tendencies have met with scepticism by many, one cannot deny the onset of a new global culture with the media environment bracketing it. In Malaysia, the privatization policy of 1985 brought active participation of the commercial sector into the media industry. Today, transnational television programmes are no longer predominantly from the United States but there are a significant number from other countries including Asian. This paper explores the patterns and consequences of media consumption on the labels and norms of young adults. A focus group study of thirty multi-ethnic young adults (20 to 25 years old) delved into labels and norms. The findings revealed that the young adults preferred media content with recurring cultural themes, action and reality genres and everyday socialization is also along ethnic lines. One Malaysia is indeed a timely and much needed policy.